The Relationship Between Heart Rate and Left Ventricular Isovolumic Relaxation During Normoxia and Hypoxia-Asphyxia in Newborn Piglets - Shen, Wei; Xu, Xin; Lee, Tze-Fun; Schmölzer, Georg; Cheung, Po-Yin (Frontiers in Physiology, 2019)
Background: Many asphyxiated neonates have cardiac complications including arrhythmia and contractile dysfunction. Little is known about the relationship between heart rate (HR) and diastolic function in asphyxiated neonates. We studied the relationship between HR and left ventricular isovolumic relaxation in neonatal asphyxia. Methods: Term newborn piglets were anesthetized and acutely instrumented with the placement of Millar catheter in the left ventricle. Hemodynamic parameters including HR, cardiac output, stroke volume, dP/dtmax and dP/dtmin, and isovolumic relaxation time constant (Tau) were continuously measured and recorded. Sixteen piglets were exposed to 50-minute normocapnic hypoxia followed by asphyxia (mean of 3.2 min) by clamping of the endotracheal tube. Sham-operated piglets (n=11) had no hypoxia nor asphyxia. The relationship between HR and other hemodynamic parameters were analyzed using Pearson Product Moment correlation test. Results: Asphyxiated piglets had cardiogenic shock and metabolic acidosis (vs. sham-operated piglets). There were significant correlations between HR and diastolic function as shown by Tau at baseline (sham-operated: r=-0.68, p=0.02; asphyxia: r=-0.55, p=0.03) and during normoxia (53 min) of sham-operated piglets (r=-0.69, p=0.02). HR and Tau was not correlated during hypoxia-asphyxia (r=-0.01, p=0.97). Cardiac output was tightly correlated with stroke volume (p<0.001) but not HR throughout the experimental period in both groups. There was no significant correlation between HR and other hemodynamic parameters during the experimental period in both groups. Conclusions: We observed an uncoupling between HR and isovolumic relaxation time constant of the neonatal heart during hypoxia-asphyxia, which deserves further studies of the relationship between HR and left ventricular diastolic function.